HEDGING STRATEGIES BY JUDGING PANELS IN TWO REALITY SHOWS: X–FACTOR VIETNAM AND X-FACTOR US = Chiến lược rào đón được sử dụng bởi ban giám khảo trong hai chương trình truyền hình thực tế: X–Factor Việt Nam và X-Factor Mỹ - Phạm, Thị Linh (2020)
This study is an attempt to examine the similarities and differences between American and Vietnamese judging panels‟ employment of hedging strategies in two reality shows: X- Factor Vietnam and X-Factor US. The research primarily focuses on the popularity and the preference of utilizing hedging strategies by two judging panels. In order to accomplish this thesis paper, the researcher has used qualitative and quantitative methods for data analysis. The data were collected from 10 episodes of X- Factor Vietnam season 1 and 10 ones of XFactor US season 2. The result gained from the finding and data analysis has revealed six hedging strategies employed by American and Vietnamese judging panels. Several major similarities and differences between American and Vietnamese judging panels‟ employment of those strategies have been presented. It is hopeful that the research could contribute to the reduction of culture shock and pragmatic failure in Vietnamese – American cross-cultural communication in real life and be a useful source of reference for the researchers in the future.